FRI0324 DISEASE ACTIVITY INDICES IN SYSTEMIC SCLEROSIS- WHICH TO USE IN DAILY PRACTICE?. (June 2019) - Groseanu, Laura; Petrescu, Sorana; Balanescu, Andra; Opris-Belinski, Daniela; Bojinca, Violeta; Berghea, Florian; Saulescu, Ioana; Daia-Iliescu, Sanziana; Mazilu, Diana; Borangiu, Andreea; Constantinescu, Cosmin; Negru, Maria Magdalena; et al.
Abstract : Background: Currently there is no fully validated index for assessing overall disease activity in patients with systemic sclerosis (SSc). Objectives: To estimate the effect of disease activity as measured by 4 disease activity indices on the risk of subsequent organ damage in a EUSTAR center cohort. Methods: Longitudinal observational study; European Systemic sclerosis study group disease activity index (EScSG DAI), revised EUSTAR disease activity index (r-EUSTAR DAI), 12 point activity index proposed by Minier (12point DAI) were calculated for all patients; the CRISS (The Combined Response Index for Systemic Sclerosis) only for patients included after 2016. Student t-test/Mann-Whitney test, chi-square test were used to evaluate differences across subgroups; Pearson's bivariate correlation/Spearman's rank correlation coefficient to evaluate the association between variables. The predictive value of various variables for major organ involvement was assessed by Roc curves and univariate regression. Results: 91 patients were selected, 77 females (84, 61%), 51, 65(13, 20) years old at diagnosis, 49, 45% diffuse subset. Disease activity scores were all higher in male patients and in patients with diffuse cutaneous involvement, digital ulcers(DU), lung fibrosis, scleroderma renal crisis (SRC), arrythmias, muscle atrophy, gastric involvement, antitopoisomerase-1 positive, EscSG DAI correlated with forced vital capacity (FVC)(r=0.73, p<0.001), DLCO(r=0.68, p<0.001), DU(x2= 3.08, p=0.05), lung fibrosis(x2=10.90, p<0.0), systolic pulmonary arterial pressure (sPAP) (r=0.54, p<0.001), muscle atrophy (x2=11, 58, p=0.001), diffuse subset (x2=11, 46, p=0.001). R- EUSTAR DAI correlated with FVC(r=0.6, p<0.001), DLCO(r=0, 58, p<0.001), diffuse subset(x2=9, 52, p<0.01), contractures(x2=11, 23, p=0.001), muscle weakness(x2= 6, 61, p=0.01), muscle atrophy (x2=10, 19, p<0.001), SRC (x2=4, 74, p=0.02) and sPAP(r=0.5, p<0.001). 12 point DAI correlated with FVC(r=0.57, p<0.001), DLCO(r=0.66, p<0.001) and sPAP(r=0.42, p<0.001). EscSG predicted well lung fibrosis (AUC=0.79, p<0.001), DU (AUC=0.66, p<0.001), gastric involvement (AUC=0.73, p<0.01) and SRC (AUC=0.9, p=0.01). R-EUSTAR index also lung fibrosis (AUC=0.76, p<0.001), DU (AUC=0.82, p<0.01) and SRC (AUC=0.84, p=0.04). 12point DAI was a good predictor for lung fibrosis(AUC=0.74, p<0.01), DU(AUC=0.78, p=0.05), gastric involvement(AUC=0.76, p=0.01). In the regression analysis, lung fibrosis(beta=0.5, 95%CI=1, 21-2, 58, p<0.01), muscle atrophy (beta=1.49, 95%CI=1.02-2.19, p=0.03) and rhythm and conduction disturbancies (beta=1.98, 95%CI=1.31-2.99, p<0.001) were independent predictors for disease activity evaluated by EScSG. For 12-EUSTAR DAI none of the evaluated parameters proved to independently contribuite to disease activity. For 12point DAI items independently contributing to disease activity were gastric involvement (beta=2.46, 95%CI=1.19-5.09, p=0.01) and muscle atrophy (beta=2.05, 95%CI=1.03-4.08, p=0.03). The CRISS cohort included 35 patients, 32 females(91, 42%), 48.48(14.24) years old, 62.85% diffuse subset, medium disease duration 11.88(7.9) months. 8 patients were excluded due to new onset or worsening of lung fibrosis or SRC. None of the patients had a CRISS score with a probability of improvement>0.6. Conclusion: We could not conclude that there is a gold standard to measure disease activity; for daily practice especially EscSG and r-EUSTAR DAI quantify and predict major organ involvement. CRISS can be useful as an outcome measure for patients with short disease duration and closely monitored in clinical studies. References: [1] K. Melsens, et al. Disease activity indices in systemic sclerosis: a systematic literature review Clin Exp Rheumatol2016; 34 (Suppl. 100):S186-S192. Disclosure of Interests: Laura Groseanu: None declared, Sorana Petrescu: None declared, Andra Balanescu Speakers bureau: multiple, Daniela Opris-Belinski Grant/research support from: GLORIA, Speakers bureau: multiple, Violeta Bojinca Speakers bureau: multiple, Florian Berghea: None declared, Ioana Saulescu: None declared, Sanziana Daia-Iliescu: None declared, Diana Mazilu Speakers bureau: Pfizer, UCB, Andreea Borangiu: None declared, Cosmin Constantinescu: None declared, Maria Magdalena Negru: None declared, Mihai Abobului: None declared, Violeta Vlad: None declared, Ruxandra Ionescu: None declared